2022
DOI: 10.1155/2022/4519982
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] MRI Diagnosis and Pathological Examination of Axillary Lymph Node Metastasis in Breast Cancer Patients

Abstract: In order to explore the characteristics and diagnostic value of magnetic resonance imaging (MRI) in axillary lymph node metastasis of breast cancer, a total of 200 breast cancer patients diagnosed and treated from January 2021 to January 2022 are selected as the study subjects, and 200 patients are divided into an axillary lymph node metastasis group and a simple breast cancer group according to pathological results. The pathological results are used as the gold standard to determine the accuracy and diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Moreover, Jiang et al ( 18 ) found that shear-wave elastography and ultrasound image features were associated with ALN metastasis. Also, the experimental results that were reported by Fu et al ( 19 ) indicated that magnetic resonance imaging (MRI) is worthy of clinical promotion and usage, based on its ability to diagnose the ALN metastasis of BC. However, MRI was limited by factors such as high sensitivity and costs, low specificity, and the long time for preliminary diagnosis ( 20 ), so its diagnostic value was not discussed in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Jiang et al ( 18 ) found that shear-wave elastography and ultrasound image features were associated with ALN metastasis. Also, the experimental results that were reported by Fu et al ( 19 ) indicated that magnetic resonance imaging (MRI) is worthy of clinical promotion and usage, based on its ability to diagnose the ALN metastasis of BC. However, MRI was limited by factors such as high sensitivity and costs, low specificity, and the long time for preliminary diagnosis ( 20 ), so its diagnostic value was not discussed in this study.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%